Grand challenge problems in technology-enhanced learning II : MOOCs and beyond : perspectives for research, practice, and policy making developed at the Alpine Rendez-Vous in Villard-de-Lans /: MOOCs and beyond : perspectives for research, practice, and policy making developed at the Alpine Rendez-Vous in Villard-de-Lans. ([2016]) - Unknown
No abstract available